2018
DOI: 10.11648/j.nano.20180602.11
|View full text |Cite
|
Sign up to set email alerts
|

Review of GaN/ZnO Hybrid Structures Based Materials and Devices

Abstract: This paper presents a review of recent advances of Gallium Nitride (GaN) and Zinc Oxide (ZnO) based hybrid structures materials and devices. GaN and ZnO have gained substantial interest in the research area of wide bandgap semiconductors due to their unique electrical, optical and structural properties. GaN and ZnO are important semiconductor materials with applications in blue and ultraviolet (UV) optoelectronics. Both materials have similar physical properties. GaN and ZnO as hybrid material have received mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 130 publications
(262 reference statements)
0
4
0
Order By: Relevance
“…The GaN/AlN heterostructure is used for high power applications [33]. Nahhas et al reported that, the formation of ZnO/GaN hybrid devices was highly flexible with superior electrical and optical properties as compared to the ZnO and GaN [34]. The improved photocatalytic performance of hybrid ZnO/GaN due to high charge carrier concentration and interlayer conductivity between ZnO and GaN thinfilm as compared to the host systems [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GaN/AlN heterostructure is used for high power applications [33]. Nahhas et al reported that, the formation of ZnO/GaN hybrid devices was highly flexible with superior electrical and optical properties as compared to the ZnO and GaN [34]. The improved photocatalytic performance of hybrid ZnO/GaN due to high charge carrier concentration and interlayer conductivity between ZnO and GaN thinfilm as compared to the host systems [34].…”
Section: Introductionmentioning
confidence: 99%
“…Nahhas et al reported that, the formation of ZnO/GaN hybrid devices was highly flexible with superior electrical and optical properties as compared to the ZnO and GaN [34]. The improved photocatalytic performance of hybrid ZnO/GaN due to high charge carrier concentration and interlayer conductivity between ZnO and GaN thinfilm as compared to the host systems [34]. ZnO is perfectly grown on GaN using molecular beam epitaxy, metal-organic chemical vapour deposition, magnetron sputtering, pulse laser deposition, etc [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the visible region of a ZnO thin film used as a solar window has a high optical transmittance [9]. Moreover, ZnO has band gap energy and optical properties identical to GaN materials, which is good for fabricating optical devices such as laser diodes (LDs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of GaN-based devices on the market has grown monotonically during recent years demonstrating interest in the upcoming technologies 7 . The list of promising GaN-based applications includes: power transistors [2], LEDs [3,4] and microwave integrated circuits, while GaN photodiodes are already commercially available (Roithner Lasertechnik GmbH).…”
Section: Introductionmentioning
confidence: 99%